Anaerobic carboxydotrophic bacteria in geothermal springs identified using stable isotope probing - Brady, Allyson L.; Sharp, Christine E.; Grasby, Stephen E.; Dunfield, Peter F. (Frontiers in Microbiology, 2015)
Carbon monoxide (CO) is a potential energy and carbon source for thermophilic bacteria in geothermal environments. Geothermal sites ranging in temperature from 45–65°C were investigated for the presence and activity of anaerobic CO-oxidizing bacteria. Anaerobic CO oxidation potentials were measured at up to 48.9 µmoles CO day-1 g (wet weight)-1 within 5 selected sites. Active anaerobic carboxydotrophic bacteria were identified using 13CO DNA stable isotope probing (SIP) combined with pyrosequencing of 16S rRNA genes amplified from labeled DNA. Bacterial communities identified in heavy DNA fractions were predominated by Firmicutes, which comprised up to 95% of all sequences in 13CO incubations. The predominant bacteria that assimilated 13C derived from CO were closely related (>98%) to genera of known carboxydotrophs including Thermincola, Desulfotomaculum, Thermolithobacter and Carboxydocella, although a few species with lower similarity to known bacteria were also found that may represent previously unconfirmed CO-oxidizers. While the distribution was variable, many of the same OTUs were identified across sample sites from different temperature regimes. These results show that bacteria capable of using CO as a carbon source are common in geothermal springs, and that thermophilic carboxydotrophs are probably already quite well known from cultivation studies.